Економічна злочинність в Україні на початку 1950-х рр. та протидія їй - Брусакова, О. В.; Brusakova, O. V.; Греченко, В. А.; Grechenko, V. A.; Оксана Брусакова (Південноукраїнський правничий часопис. - 2023. - № 3. - С. 234-240, 2023)
Досліджено основні аспекти економічної злочинності та діяльність міліції щодо протидії їй у 1950-1952 рр. Виявлено головні чинники, що впливали на генезу економічної злочинності у вказаний період. Охарактеризовано стан економічної злочинності, її основні прояви у досліджувані роки. Проаналізовано основні заходи міліції у боротьбі з економічною злочинністю.

The causes and main manifestations of economic crime in Ukraine at the beginning of the 1950s are revealed, its features are revealed, and the main areas of militia activity in countering it are revealed. The economy of the totalitarian state, with its over-centralization, with the dominance of heavy industry to the detriment of agriculture, the service sector, light industry, and the production of consumer goods, objectively created conditions for economic crime. At the beginning of the 1950s, the consequences of the war and post-war devastation had not yet been completely overcome. All this led to a stable and high level of economic crime. The largest number of embezzlements occurred in trade organizations, supply and sales institutions, enterprises of the meat, dairy, and textile industries. The very fact of the existence of rationed trade contributed to massive embezzlement by trade workers admitted to distribution. The criminalization of society was especially visible in the most common type of crime – petty theft. At the same time, embezzlement occurred in almost all spheres of the economy. Economic organized crime, which was born, successfully filled the gaps of the socialist economy, taking upon itself the responsibility of providing the unsatisfied needs of the population through criminal means with great benefit for itself. In this regard, the state tried to strengthen criminal responsibility for committing these types of crimes, and the leadership of the Ministry of Internal Affairs of the Republic – to intensify the activities of the militia in the prevention and detection of these crimes, improving the activities of its agents in trade and cooperative organizations, strengthening the departments for combating the theft of socialist property and speculation. A certain step on the way to improving the organization of this service in September 1951 was the quantitative increase of BRSV apparatuses and their qualitative strengthening, as well as the transition to the linear and branch principle of activity.

Исследованы основные аспекты экономической преступности и деятельность милиции по противодействию ей в 1950-1952 гг. Выявлены главные факторы, влиявшие на генезу экономической преступности в указанный период. Охарактеризованы состояние экономической преступности, ее основные проявления в изучаемые годы. Проанализированы основные меры милиции по борьбе с экономической преступностью.
Economic crime in Ukraine in the early 1950s and its counteraction
Keywords: історико-правовий аналіз; historical and legal analysis; историко-правовой анализ; економічна злочинність; economic crime; экономическая преступность; міліція; militia; милиция; Міністерство внутрішніх справ; Ministry of Internal Affairs; Министерство внутренних дел; Україна; Ukraine; Украина; 1950–1952; розкрадання державної власності; theft of state property; хищение государственной собственности; фальшивомонетництво; counterfeiting; фальшивомонетничество; спекуляція; speculation; спекуляция; протидія злочинності; crime prevention; противодействие преступности